2020
DOI: 10.1371/journal.pone.0229077
|View full text |Cite
|
Sign up to set email alerts
|

Novel EGFR ectodomain mutations associated with ligand-independent activation and cetuximab resistance in head and neck cancer

Abstract: Epidermal growth factor receptor (EGFR) is a pro-tumorigenic receptor tyrosine kinase that facilitates growth for cancer cells that overexpress the receptor. Monoclonal anti-EGFR antibody Cetuximab (CTX) provides significant clinical benefit in patients with head and neck squamous cell carcinoma (HNSCC). Missense mutations in the ectodomain (ECD) of EGFR can be acquired under CTX treatment and mimic the effect of large deletions on spontaneous untethering and activation of the receptor. Little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…This can primarily be attributed to a deregulation of EGFR itself (overexpression and strong activity in more than 80% of HNSCC) [ 42 , 43 ], the expression of a mutant type III variant of EGFR [ 44 , 45 ], aberrant downstream signaling pathways [ 46 , 47 , 48 ], an oncogenic switch [ 49 , 50 , 51 , 52 ] or compensatory mechanisms (such as the activity of other tyrosine-kinase receptor ALK [ 53 ], MET [ 54 , 55 ] or AXL [ 56 , 57 ]). CTX even seems to promote its own resistance by inducing mutations in KRAS/NRAS/HRAS [ 58 ] or missense mutations in the ectodomain of EGFR, mimicking the activation of the receptor [ 59 ]. In this study, we reported that Cav1 may also play a role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…This can primarily be attributed to a deregulation of EGFR itself (overexpression and strong activity in more than 80% of HNSCC) [ 42 , 43 ], the expression of a mutant type III variant of EGFR [ 44 , 45 ], aberrant downstream signaling pathways [ 46 , 47 , 48 ], an oncogenic switch [ 49 , 50 , 51 , 52 ] or compensatory mechanisms (such as the activity of other tyrosine-kinase receptor ALK [ 53 ], MET [ 54 , 55 ] or AXL [ 56 , 57 ]). CTX even seems to promote its own resistance by inducing mutations in KRAS/NRAS/HRAS [ 58 ] or missense mutations in the ectodomain of EGFR, mimicking the activation of the receptor [ 59 ]. In this study, we reported that Cav1 may also play a role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations may lead to conformational changes in the extracellular regions of EGFR, resulting in the induction of ligand-independent EGFR phosphorylation ( 48 , 49 ). Furthermore, the G33K and N56K mutations, which are also located in domain I, cause ligand-independent EGFR phosphorylation in head and neck cancer ( 50 ). These mutations may also cause abnormal phosphorylation by altering EGFR structural dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of uptake was dependant on the cell line, as it was significantly higher in the KYSE-30 compared to CAL-27 cancer cells. We hypothesise that the increased number of AuNRs in EGFR positive cancer cells is likely due to ligand-receptor binding activity [37] as opposed to simple passive diffusion mechanism or other forms of endocytosis. The work of Van Lehn et al showed increased internalisation of AuNPs into HeLa cells when incubated at 37 ℃ compared to ℃, depending on their size and functionalisation [38], indicating the importance of active transport for the cell internalisation of nanoparticles.…”
Section: Taunrs But Not Uaunrs Are Increasingly Associated With Egfr-mentioning
confidence: 98%